HISEC: a new lightweight block cipher algorithm - Alshaikhli, Imad Fakhri Taha; Mahmood Al Dabbagh, Sufyan Salim; Alahmad, Mohammad (2014)
Lightweight block cipher algorithms are vital for constrained environment. There are many applications need secured lightweight block cipher algorithm like credit card, E-passport and etc. In this paper, we propose a new lightweight block cipher algorithm called HISEC. We applied three attacks differential, integral attacks and boomerang attack. The results showed that HISEC is better than some lightweight algorithms.